Exploring the relationship between shifts in high-density lipoprotein (HDL) particle subclass distribution/functionality and cardiac function in doxorubicin (DOX)-induced cardiotoxicity - Abrahams, Carmelita Bianca (Department of Medicine, 2024)
Introduction: Elucidating the mechanisms involved in cardiotoxicity that develops in cancer patients receiving doxorubicin (DOX) chemotherapy is key to identify potential cardioprotective strategies and early biomarkers in these patients. Both breast cancer and DOX treatment are associated with dyslipidaemia, however changes in high-density lipoprotein (HDL) particle subclass distribution, composition and functionality are unknown. We therefore aimed to investigate whether changes in HDL particle subclass distribution, composition and functionality in breast cancer patients and tumour bearing mice receiving DOX chemotherapy may contribute to cardiac dysfunction. Methods: Blood samples were collected in 34 female breast cancer patients (18-65 years old with no co-morbidities) prior (B) to and after completion (E) of DOX chemotherapy (6 cycles every 3 weeks). Breast cancer was induced in female C57/Bl6 mice (6-8 weeks old) by subcutaneous injection of the E0771 cell line. Once a palpable tumour formed, DOX (5 mg/kg, i.p.) was given weekly for 5 weeks. The following groups were considered: Control (C, n=17), DOX (D, n=17), Tumour (T, n=20) and DOX+Tumour (DT, n=17). Cardiac function was measured with echocardiography, and serum was collected at baseline (B) and at endpoint (E). In serum, HDL subclass distribution was measured using the Lipoprint® system. HDL anti-oxidative functionality was assessed by measuring paraoxonase-1 (PON1) activity. The ability of isolated HDL particles to protect against DOX-induced cytotoxicity was assessed in H9C2 cells and measured using the adenosine-triphosphate (ATP) assay. Results: DOX-induced subclinical cardiotoxicity was observed in 9 breast cancer patients. DOX therapy reduced the intermediate HDL subclasses [52.5±1.0% (B) vs 48.6±0.9% (E), p<0.001], an effect that correlated with cardiac dysfunction in patients (r =+0.29, p<0.05). In the mouse model, DOX induced cardiac alterations by reducing radial strain of the left ventricular anterior wall [D: 49.96±2.3% (B) vs 21.8±2.9% (E), p<0.0001 and DT: 46.7±2.7% (B) vs 31.7±4.4% (E), p<0.01]. In mice, breast cancer reduced the intermediate HDL subclasses (D: 74.8±1.2% vs DT: 67.7±2.4%, p<0.001) and increased the large HDL subclasses (D: 24.0±1.2% vs DT: 30.9±2.3%, p<0.001), while DOX treatment increased the small HDL subclasses (T: 0.3±0.2% vs DT: 0.9±0.5%, p<0.05). DOX treatment in breast cancer mice was associated with reduced PON1 activity (C: 0.4±0.0% vs DT: 0.2±0.0%, p<0.05). Interestingly, a reduction in the intermediate HDL subclass, HDL-4, and PON1 activity were associated with a reduction in radial strain of the left ventricular anterior wall (r=+0.41, p<0.05 and r=+0.44, p<0.05, respectively). Most importantly, HDL particles isolated from breast cancer or DOX treated mice could not protect against DOX-induced cytotoxicity in H9C2 cells compared to HDL particles isolated from control mice (C: 100.0±16.6 ATP% vs D: 49.3±11.9 ATP% or T: 52.44±19.8 ATP%, p<0.05 vs C). Conclusion: In breast cancer patients and in tumour bearing mice, a treatment with DOX was associated with a shift in HDL subclass distribution and functionality that correlated with cardiac alterations. This change in HDL particle dynamic caused it to lose its cardioprotective functionality against DOXinduced cardiotoxicity, thus suggesting that HDL particles may play a key role in the development of cardiotoxicity associated with DOX chemotherapy. Our data therefore highlight HDL particles as a potential therapeutic target to limit DOX-induced cardiotoxicity. Our study also improves upon prior research by including a cancer environment in our mouse model of DOX-induced cardiotoxicity and highlights the contribution of the cancer to the pathophysiological changes observed.